2021
DOI: 10.1002/jmri.28019
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging‐Based Radiomics Features Associated with Depth of Invasion Predicted Lymph Node Metastasis and Prognosis in Tongue Cancer

Abstract: Background Adequate safe margin in tongue cancer radical surgery is one of the most important prognostic factors. However, the role of peritumoral tissues in predicting lymph node metastasis (LNM) and prognosis using radiomics analysis remains unclear. Purpose To investigate whether magnetic resonance imaging (MRI)‐based radiomics analysis with peritumoral extensions contributes toward the prediction of LNM and prognosis in tongue cancer. Study type Retrospective. Population Two hundred and thirty‐six patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…At the current time only four studies focused on MRIbased radiomics in oral cavity cancer and only one focused on survival outcomes. 26 Frood et al 27 (2018) conducted a retrospective study on 115 cases of oral cavity SCC to detect MRI radiomic textures indicative of lymphadenopathy with ENE. Nodal entropy derived from CE-T1 was significant in predicting ENE and nodal entropy combined with irregular boundary was the best predictor of ENE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the current time only four studies focused on MRIbased radiomics in oral cavity cancer and only one focused on survival outcomes. 26 Frood et al 27 (2018) conducted a retrospective study on 115 cases of oral cavity SCC to detect MRI radiomic textures indicative of lymphadenopathy with ENE. Nodal entropy derived from CE-T1 was significant in predicting ENE and nodal entropy combined with irregular boundary was the best predictor of ENE.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study of radiomics for OTSCC that includes multiple MRI sequences and survival outcomes as clinical endpoints. At the current time only four studies focused on MRI‐based radiomics in oral cavity cancer and only one focused on survival outcomes 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics is an advanced method for quantitative analysis that can reveal information from microscopic features that are not easily observable by the naked eye in medical imaging (17,36). In recent years, various studies have attempted to predict LNM based on MRI radiomic analysis of primary lesions (22,(37)(38)(39)(40)(41)(42)(43). To the best of our knowledge, only one study has analyzed the predictive efficacy of radiomics based on MRI for LNM of PDAC (43), but only the arterial phase of the T1WI enhanced sequence was used.…”
Section: Discussionmentioning
confidence: 99%
“…Kudoh et al ( 39 ) also found that the model based on positron emission tomography radiomics features performed well in predicting cervical lymph node metastasis in TSCC. Wang et al ( 40 ) showed that models based on MR radiomics signature from the primary tumor with 10 mm peritumoral extensions and clinicopathological characteristics had the highest AUC of 0.995 in the training cohort and 0.872 in the testing cohort. These satisfactory results have revealed the promising prospect of ML.…”
Section: Applications Of ML In Tsccmentioning
confidence: 99%